การศึกษาเครือข่ายสังคมการสื่อสารด้านการใช้ยาของบุคลากรการแพทย์ ด้วยการวิเคราะห์เครือข่ายสังคม - ชัยชนะวิโรจน์, อุไรวรรณ; กองแก้ว, ชื่นจิตร (Journal of The Royal Thai Army Nurses, 2016)
การวิจัยครั้งนี้เป็นการวิจัยเชิงพรรณนา มีวัตถุประสงค์เพื่อศึกษาลักษณะเครือข่ายสังคมการสื่อสารด้านการใช้ยาของบุคลากรการแพทย์ เก็บข้อมูลในบุคลากรทางการแพทย์จากโรงพยาบาล 3 แห่ง ในเขตภาคเหนือตอนล่าง มีอัตราการตอบกลับร้อยละ 83 มีกลุ่มตัวอย่างจำนวน 277 คน โดยใช้แบบสอบถามการขอคำปรึกษาด้านการใช้ยา วิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนาและการวิเคราะห์เครือข่ายสังคมด้วยข้อมูลเชิงสัมพันธ์และแผนภาพเครือข่ายผลการวิจัย พบว่ากลุ่มตัวอย่าง ส่วนใหญ่เป็นเพศหญิง (ร้อยละ 89) มีอายุเฉลี่ย 38 ปี มีประสบการณ์การทำงานเฉลี่ย 13.4 ปี ส่วนใหญ่จบการศึกษาระดับปริญญาตรี (ร้อยละ 70) และส่วนใหญ่เป็นพยาบาลวิชาชีพ (ร้อยละ 58.9) การวิเคราะห์ข้อมูล พบว่าเครือข่ายสังคมการสื่อสารด้านการใช้ยาของโรงพยาบาลทั้งสามแห่งมีความหนาแน่นต่ำ (Density = 0.03, SD = 0.16) มีค่าสัมประสิทธิ์การจัดกลุ่มต่ำ (weighted CC = 0.07 - 0.11) และโรงพยาบาลทั้งสามแห่งมีค่าความเป็นศูนย์กลางปานกลาง (network centralization = 35.60 - 57.50%) การวิเคราะห์แผนภาพเครือข่ายแสดงให้เห็นว่าส่วนใหญ่เภสัชกรมีความเป็นศูนย์กลางของการปรึกษาหารือด้านการใช้ยาสูง การวิจัยนี้แสดงตัวอย่างการใช้การวิเคราะห์เครือข่ายสังคมเพื่ออธิบายลักษณะเครือข่ายสังคมของการสื่อสารด้านการใช้ยาของกลุ่มบุคลากรทางการแพทย์ ลักษณะของโครงสร้างเครือข่ายสังคมสะท้อนความตระหนักและตื่นตัวเกี่ยวกับความปลอดภัยในการใช้ยา The Study of Communication Social Networks in Medical Usage among Health Care Providers by Usinga Social Network Analysis This descriptive study aimed to examine characteristics of social networks in drug use among health care providers. Using themedication consultation questionnaires, data collection was conducted in 277 health care providersfrom 3 hospitals in lower northern region of Thailand, with a response rate of 83%. Data analysis included descriptive statistics and social network analysis of relational data and sociograms. The results showed that most subjectswere female (89 %) with the average age of 38 years and work experience of 13.4 years. The majority of the subjects finished Bachelor degree (70%). More than half were registered nurses (58.9%). Social network analysis revealed thatthe density of threehospital networks were loose (Density = 0.03, SD = 0.16) with low clustering coefficient (weighted CC = 0.07 - 0.11). All 3 networks had moderate degree of centralization (network centralization = 35.60 - 57.50%). Network sociograms revealed that most of pharmacists were the center of medication consultation networks.This study demonstrated how social network analysis was used to describe safety cultureofdrug use among health care providers. Structure of social networks characteristics reflected the awareness and alertness in safetyof medication use.